Rules of origin for development: From GSP to global free trade - Jeremy T. Harris (Inter-American Development Bank (IDB), 2009)
Recent calls for reform of the rules of origin in preferential trade arrangements such as the GSP as well as in many free trade agreements between developed and developing countries have focused almost exclusively on the need to relax the requirements of these rules. Without fundamentally disagreeing, his paper presents some cautionary arguments with respect to the relationship between rules of origin and development, and proposes an alternative mechanism, extended cumulation, by which the problems generated by burdensome rules of origin might be alleviated without jeopardizing the development benefits for which the preferential programs were intended. In the longer-term, this approach could also alter the political economy balance within high-tariff developing countries, increasing the potential for more substantive multilateral liberalization.
hdl:11319/2492
Keywords: 330